Reliability of a point-of-care device to determine oxidative stress in whole blood before and after acute exercise: A practical approach for the applied sports sciences. Issue 6 (19th March 2021) - Quinn, Karlee M.; Cox, Amanda J.; Roberts, Llion A.; Briskey, David; Minahan, Clare
ABSTRACT: Measuring alterations in redox homoeostasis in athletes can provide insights into their responses to training such as adaptations or fatigued states. However, redox monitoring is impractical in athletes given the time burden of venepuncture and subsequent laboratory assays. The ability of point-of-care tests (POC): 1) Free Oxygen Radical Test (FORT) and 2) Free Oxygen Radical Defence (FORD), to reliably measure whole blood oxidative stress between days and after exercise is unknown as well as their relationship with laboratory measures (F2-isoprostanes, total antioxidant capacity; TAC). Participants completed two trials performed on separate days comprising blood sampling at rest (n=22) and after treadmill-running (n=14). Between-day CVs for FORT (4.6%) and FORD (4.8%) were acceptable at rest. There was no difference in the between-day magnitude of change in any biomarker from pre- to post-exercise (p>0.05), yet the within-trial change in FORD was variable (trial one: +4.5%, p=0.15; trial two: +6.3%, p<0.05). TAC and FORD were significantly correlated pre- and post-exercise (r=~0.53, p<0.05), whereas F2-isoprostanes and FORT had a significant correlation pre-exercise only (r=0.45, p=0.03). Overall, the POC tests are reliable and could be used for baseline longitudinal redox monitoring. More data is required on POC tests for assessing redox perturbations induced by exercise.